The Mediating Role of Energy Efficiency Measures in Enhancing Organizational Performance: Evidence from the Manufacturing Sector in Jordan - Almarshad, Mohammad Nassar; Alwaely, Suad Abdalkareem; Alkhawaldeh, Bashar Younis; Al Qaryouti, Mosa Qasim Hasan; Ahmad, Ahmad Y. A. Bani (International Journal of Energy Economics and Policy, 2024)
This study investigates the mediating role of energy efficiency measures in enhancing manufacturing firm performance in Jordan. A conceptual model is developed linking organizational policies, culture, and government incentives to adoption of energy efficiency measures, which in turn impact organizational performance. Data was collected through a survey of 300 manufacturing firms across major industrial sub-sectors in Jordan including food, textiles, chemicals, pharmaceuticals, construction materials, and machinery. Structural equation modeling using SmartPLS software tested the hypothesized relationships. Results provide empirical support for the conceptual framework. Organizational policies, culture emphasizing environmental responsibility, and government incentives positively influence adoption of energy efficiency measures like process optimization, equipment upgrades, and lighting improvements. Greater adoption of these measures enhances manufacturing performance across various dimensions like efficiency, quality, flexibility, and competitiveness. Further, energy efficiency measures strongly mediate the links between organizational policies, culture, incentives and manufacturing performance. The study makes important theoretical contributions to the resource-based view and natural resource-based view in a developing economy context. It also offers actionable implications for manufacturing managers and policymakers regarding energy efficiency strategies and programs. Limitations relating to the cross-sectional design, self-reported data, and generalizability are discussed along with recommendations for future research using longitudinal, qualitative, and multilevel approaches. Overall, the study highlights energy efficiency as a critical capability for boosting competitiveness in manufacturing firms, with mediation analysis elucidating the underlying performance enhancement mechanisms.